Administration of a Salmonella Enteritidis ΔhilAssrAfliG strain by coarse spray to newly hatched broilers reduces colonization and shedding of a Salmonella Enteritidis challenge strain. (22nd December 2014) - De Cort, W.; Haesebrouck, F.; Ducatelle, R.; van Immerseel, F.
Abstract : Consumption of contaminated poultry meat is still an important cause of Salmonella infections in humans. Colonization inhibition (CI) occurs when a live Salmonella strain is administered to chickens and subsequently protects against challenge with another Salmonella strain belonging to the same serotype. A Salmonella Enteritidis hilAssrAfliG deletion mutant has previously been proven to reduce colonization and shedding of a wild-type Salmonella Enteritidis strain in newly hatched broilers after experimental infection. In this study, we compared two administration routes for this strain. Administering the Salmonella Enteritidis Δ hilAssrAfliG strain through drinking water on the first day of life resulted in decreased fecal shedding and cecal colonization of a wild-type Salmonella Enteritidis challenge strain administered 24 h later using a seeder-bird model. When administering the CI strain by coarse spray on newly hatched broiler chicks, an even more pronounced reduction of cecal colonization was observed, and fecal shedding of the Salmonella Enteritidis challenge strain ceased during the course of the experiment. These data suggest that administering a Salmonella Enteritidis Δ hilAssrAfliG strain to newly hatched chicks using a coarse spray is a useful and effective method that reduces colonization and shedding of a wild-type Salmonella Enteritidis strain after early challenge.